Peran Taman Pendidikan Al-Qur'an (TPQ) dalam Pengembangan Akhlak Anak - Masnawati, Eli; Fitria, Salva Nur (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This literature research examines the role of the Al-Qur'an Education Park (TPQ) in the formation of children's morals in Indonesia. Through a systematic analysis of current literature, this research reveals TPQ's strategic position as a non-formal religious education institution that not only focuses on teaching the Koran but also plays an important role in instilling Islamic values and character formation. Factors influencing the effectiveness of TPQ were identified, including teacher quality, curriculum, family and community support, and program consistency. This research proposes a conceptual model for TPQ development that emphasizes a holistic approach, including an integrative curriculum, teacher competency development, active learning methods, a comprehensive evaluation system, and tri-centre educational partnerships. The main challenges in developing TPQ include quality standardization, limited resources, adaptation to social change, and synergy with formal education. Significant opportunities were also identified, including national policy support, increased public awareness, and potential technology integration. Policy and practice implications are formulated, including strengthening regulations, increasing teaching capacity, and innovating learning methods. This research concludes that TPQ has great potential to contribute to the formation of a generation with noble morals, but requires systematic and sustainable efforts from various stakeholders to realize this potential.